Influence of Personal Values and Knowledge Sharing on Employee Performance with Job Satisfaction as a Mediating Variable at PDAM Perumda Tirta Hidayah in Bengkulu City - Naim, Muhaimin; Praningrum, Praningrum (Student Journal of Business and Management, 2023)
PDAM Perumda Tirta Hidayah Bengkulu city as a regional company responsible for providing clean water services in urban areas has an important role. In accordance with this, of course the PDAM must maintain the performance of its employees in order to provide maximum service. Performance is the level of good or bad work given by someone and the amount of work given by someone in carrying out their responsibilities as a worker. This study aims to examine the effect of personal values, knowledge sharing on performance mediated by job satisfaction. The type of research used is quantitative research, with a research design that is a survey design. The data used is primary data obtained directly from respondents using a questionnaire. The population in this study were employees who worked at PDAM Perumda Tirta Hidayah Bengkulu City. This study has 48 statements given to respondents. The number of respondents in this study who were processed was 245 respondents. The analysis tool in this study used SPSS. The results of this study explain that personal value has a positive and significant effect on job satisfaction, personal value has a positive and significant effect on employee performance, knowledge sharing has a positive and significant effect on job satisfaction, knowledge sharing has a positive and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance, job satisfaction mediates the effect of personal value on employee performance, and job satisfaction mediates the effect of knowledge sharing on employee performance